EFEKTIVITAS KATEPAY SEBAGAI ALAT PEMBAYARAN DIGITAL PELAJAR DI KOTA SURABAYA - Laila Krisna Arti; Ririt Iriani Sri Setiawati (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Katepay is an innovation introduced by the Surabaya City Population an Civil Registration Department by untilizing Child Identity Cards (KIA) as a non-cash payment tool. This initiative aims to provide students with the opportunity to learn and understand digital transactions from an early age. This research aims to evaluate the effectiveness of the Katepay program in the context of its use by students, parents, and collaborating partners. This type of research is descriptive using a qualitative approach. The research results show an increase in students understanding of non-cash transactions through the use of Katepay. Parents also benefit from the security and comfort aspects of using Katepay. This program also provides a positive experience for sellers and outlets who collaborate in accepting payments through KIA. Thus, several challenges to program implementation were also identified as well as several factors that could support the success of the program.